IMPLEMENTASI TRANSFORMASI FOURIER UNTUK MENGURANGI NOISE PADA GAMBAR DIGITAL DENGAN MENGGUNAKAN MATLAB - susilowati, emi (Just IT, 2011)
Picture digital or digital image is aÃÂ  two dimensional matriks, which in the each elements of picture called pixel represent the grey level. At digital image the information is discrete. Image processing is a process to transfer image on certain domain or the another dimension. In this research, oducted transformation of spatial domain to frequence domain using algorithm fourier transform.